Characterization of Antimicrobial Activities of Pediococcus pentosaceus Vtcc-B-601 - Dat Nghe and Tu Nguyen (Journal of Applied Pharmaceutical Science, 2014)
In this study, Pediococcus pentosaceus VTCC-B-601 was investigated and characterized for bacteriocin production. The antimicrobial activities were produced strongly at the late exponential phase (5x108 CFU/ml), corresponding to the activity of cephalosporin (13.3µg/ml) against Salmonella typhimurium ATCC 19430, Pseudomonas aeruginosa ATCC 27853, Staphylococus aureus ATCC 25923, and Micrococcus luteus ATCC 10240. The bacteriocin activity was reduced after proteinase K treatment while the activity was still stable in high temperature. This work supplied a Pediococcus pentosaceus bacteriocin identification that was useful in food preservation, clinical use, and agriculture.
Keywords: Antimicrobial activities, bacteriocin, Pediococcus pentosaceus VTCC-B-601, thermostability